2019
DOI: 10.2147/ndt.s201620
|View full text |Cite
|
Sign up to set email alerts
|

<p>The relationship between serum cobalamin, folic acid, and homocysteine and the risk of post-cardiac surgery delirium</p>

Abstract: Purpose: It has been reported that cobalamin and folate deficiency is related to delirium in persons with dementia. We evaluated the association of admission serum levels of cobalamin, folic acid, and homocysteine with the occurrence of acute delirium after coronary artery bypass surgery. Methods: In this prospective cohort study, serum levels of cobalamin, folic acid, and homocysteine were measured for 296 patients upon admission. Delirium was defined by the confusion assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Preoperative plasma homocysteine is associated with postoperative delirium in patients after cancer surgery ( Weerink et al, 2018 ) or hemiarthroplasty ( Guo et al, 2020 ). However, another study showed no association between preoperative plasma homocysteine and the incidence of postoperative delirium in patients with cardiac surgery ( Vahdat Shariatpanahi et al, 2019 ). Here, we showed that participants with postoperative delirium had higher median preoperative plasma concentrations of homocysteine than participants without postoperative delirium after hip or knee surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative plasma homocysteine is associated with postoperative delirium in patients after cancer surgery ( Weerink et al, 2018 ) or hemiarthroplasty ( Guo et al, 2020 ). However, another study showed no association between preoperative plasma homocysteine and the incidence of postoperative delirium in patients with cardiac surgery ( Vahdat Shariatpanahi et al, 2019 ). Here, we showed that participants with postoperative delirium had higher median preoperative plasma concentrations of homocysteine than participants without postoperative delirium after hip or knee surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteine (elevated plasma homocysteine concentration) is a potential predisposing factor owing to its involvement in cardiovascular disease ( Refsum et al, 1998 ) and AD ( Morris, 2003 ). Preoperative plasma hyperhomocysteine concentration is associated with postoperative delirium ( Kim et al, 2015 ; Weerink et al, 2018 ), but conflicting results exist ( Vahdat Shariatpanahi et al, 2019 ; Guo et al, 2020 ). Moreover, hyperhomocysteine increases blood-brain barrier (BBB) permeability ( Kamath et al, 2006 ; Beard et al, 2011 ) and promotes neuroinflammation, which can lead to cognitive dysfunction ( Adamis et al, 2009 ; Varatharaj and Galea, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe CblD in the elderly may predispose to delirium, 45 , 50 , 51 although this association has been confuted by a recent report. 52 …”
Section: Neuropsychiatric Impairmentmentioning
confidence: 99%
“…Severe CblD in the elderly may predispose to delirium, 45,50,51 although this association has been confuted by a recent report. 52 Of note, recent trials do not support Cbl supplementation in the elderly with normal to low Cbl levels for preventing cognitive deterioration. 53,54 Other Manifestations.…”
Section: Dietary Poor Intakementioning
confidence: 99%